Nanocomposite-based PCR reactors to enhance thermal rate and fluorescence intensity in hand-held qPCR device - Han, Jiyeon; A M, Tiara; Kim, Seongryeong; Morales Florez, Gabriela; Shrestha, Kiran; Nguyen, Dang Du; Kim, Inki; Lee, Jinkee; Cho, Gyoujin (Journal of nanobiotechnology, 2025)
A photonic quantitative polymerase chain reaction (qPCR) has usually implemented a polydimethylsiloxane (PDMS) based disposable inexpensive PCR reactor, worked as the photothermal cycler, to show potential as a point-of-care test (PoCT) for detection nucleic acids. However, the PoCT type photonic qPCR has to overcome the prolonged time for the fabrication of PDMS-based PCR reactors and enable a rapid thermal cycler to shorten diagnosis time with a strong fluorescence intensity. Here, we developed a room-temperature curable titanium dioxide (TiO 2 ) nanoparticle dispersed PDMS (TiO 2 -PDMS) nanocomposite to reduce the fabrication time of the PCR reactor which enhanced the speed of photothermal cycles and fluorescence signal intensity of photonic qPCR. The TiO 2 -PDMS nanocomposite was formulated for rapid cross-linking at the room-temperature by introducing an optimized amount of Pt catalyst, resulting in the fabrication of a nanocomposite-based PCR reactor within 8 min at room-temperature. The nanocomposite-based PCR reactor enhanced the heating rate to 18.33 Cº/s and cooling rate to −3.11Cº/s because of the phonon scattering effect of TiO 2 in the reactor and successfully amplified λ-DNA (amplicon size of 100 bp) within 10 min. Finally, we improved the qPCR efficiency by 2 cycle threshold ( C t ) value compared with pristine PDMS reactor and quantified up to 10 copies/µL nucleic acids by fluorescence intensity enhancement resulting from light reflections property of TiO 2 . By using TiO 2 -PDMS nanocomposite-based PCR reactors, the fast and efficient nucleic acid assay was enabled without loss of sensitivity, and it can be practically used in the field of PoCT. Graphical Abstract